Transdisciplinary Research: Can Citizen Science Support Effective Decision-Making for Coastal Infrastructure Management? - Agnew, Sonya; Kopke, Kathrin; Power, Orla-Peach; Troya, María Del Camino; Dozier, Amy (Frontiers in Marine Science, 2022)
Stakeholder engagement is increasingly recognised as imperative for developing effective climate change adaptation policy within the EU, particularly for delivering sustainable coastal infrastructure. This perspective discusses how current transdisciplinary research (TDR) approaches concerning ecoengineering solutions for artificial coastal structures are insufficient in ensuring adequate stakeholder engagement to facilitate coherent and enduring decision-making and policy development processes. Socio-cultural analysis focussing on how people view and feel about artificial coastal infrastructure within coastal infrastructure research has been recognised as a large knowledge gap. We suggest that citizen science (CS) methodologies as part of a cultural ecosystem services (CES) research approach can adequately inform and support the implementation of ecoengineering solutions for hard artificial coastal structures whilst addressing existing barriers associated with stakeholder engagement in current TDR approaches.